Parathyroid Function in Primary Osteoporosis - Riggs, B. Lawrence (1973)
Two major species of serum immunoreactive parathyroid hormone (iPTH) were measured in 47 untreated patients with primary osteoporosis by using two highly specific radioimmunoassays. Mean iPTH was normal with one antiserum but was lower than normal (P < 0.001) with the other, iPTH values did not correlate with biochemical parameters or with the proportion of bone-resorbing surfaces in iliac crest bone biopsy specimens. These data suggest that the increased bone resorption is not due to increased parathyroid function in most osteoporotic patients. However, seven of our patients (15%) appear to represent a separate population because they had increased values with one or the other of the antisera.